Etnoekologi Masyarakat di Kawasan Hutan Jati Kabupaten Batang pada Pertanaman Tumpangsari (Jurnal Jejaring Matematika dan Sains, 2021)
Local knowledge is substantially the prevailing norm in a society that is believed to be true and becomes a reference in acting and behaving daily. Some people in the teak forest area in the Pecalungan Village, Batang Regency, make a living as farmers by utilizing the teak forest area. In managing the land of forest workers, according to the rules that have been passed down from generation to generation, the land management guidelines with these techniques are local knowledge that needs to be studied through ethnoecological studies. This study aims to describe the interaction of forest workers with the teak forest environment related to intercropping, namely cayenne pepper, long beans and corn with teak trees. The method used in this research is descriptive qualitative. Data collection using in-depth interviews with three informants (forest workers) using interview guidelines. Each interview activity was recorded. Data collection also uses the observation method and each activity is documented in the form of photos. The results showed that forest workers had knowledge of intercropping and applied it in their lives, namely the knowledge of selecting plant species suitable for teak; knowledge of time and soil characteristics suitable for plants; knowledge of making natural fertilizers; knowledge of cropping patterns; knowledge of plant maintenance; harvest time knowledge; and forest worker traditions. All cultivation activities carried out by forest workers are based on an understanding of the sustainability of teak forests.